Serotype-dependent adhesion of Shiga toxin-producing Escherichia coli to bovine milk fat globule membrane proteins - Arthur Bagel; Christelle Lopez; Elisabeth David-Briand; Valérie Michel; Thomas Douëllou; Delphine Sergentet; Delphine Sergentet (Frontiers in Microbiology, 2022)
Shiga toxin-producing Escherichia coli (STEC) are food-borne pathogens that can cause severe symptoms for humans. Raw milk products are often incriminated as vehicule for human STEC infection. However, raw milk naturally contains molecules, such as the milk fat globule membrane and associated proteins, that could inhibit pathogen adhesion by acting as mimetic ligands. This study aimed to: (i) evaluate the capability of STEC cells to adhere to bovine milk fat globule membrane proteins (MFGMPs), (ii) highlight STEC surface proteins associated with adhesion and (iii) evaluate the variation between different STEC serotypes. We evaluated the physicochemical interactions between STEC and milk fat globules (MFGs) by analyzing hydrophobic properties and measuring the ζ-potential. We used a plate adhesion assay to assess adhesion between MFGMPs and 15 Escherichia coli strains belonging to three key serotypes (O157:H7, O26:H11, and O103:H2). A relative quantitative proteomic approach was conducted by mass spectrometry to identify STEC surface proteins that may be involved in STEC-MFG adhesion. The majority of E. coli strains showed a hydrophilic profile. The ζ-potential values were between −3.7 and − 2.9 mV for the strains and between −12.2 ± 0.14 mV for MFGs. Our results suggest that non-specific interactions are not strongly involved in STEC-MFG association and that molecular bonds could form between STEC and MFGs. Plate adhesion assays showed a weak adhesion of O157:H7 E. coli strains to MFGMPs. In contrast, O26:H11 and O103:H2 serotypes attached more to MFGMPs. Relative quantitative proteomic analysis showed that the O26:H11 str. 21,765 differentially expressed five outer membrane-associated proteins or lipoproteins compared with the O157:H7 str. EDL933. This analysis also found strain-specific differentially expressed proteins, including four O26:H11 str. 21,765-specific proteins/lipoproteins and eight O103:H2 str. PMK5-specific proteins. For the first time, we demonstrated STEC adhesion to MFGMPs and discovered a serotype effect. Several outer membrane proteins—OmpC and homologous proteins, intimin, Type 1 Fimbriae, and AIDA-I—that may be involved in STEC-MFG adhesion were highlighted. More research on STEC’s ability to adhere to MFGMs in diverse biological environments, such as raw milk cheeses and the human gastrointestinal tract, is needed to confirm the anti-adhesion properties of the STEC-MFG complex.